Meningkatkan Harmonisasi dan Toleransi melalui Seminar Moderasi Beragama di Desa Ladang Peris Kecamatan Bajubang Kabupaten Batang Hari - Sukatin Sukatin; Maisarah Gusvita; Anisa Pertiwi; Rahma Rahma; Moch. Zidhane Saputra (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Indonesia is known as a country with one of the most diverse tribes, cultures, ethnicities, languages ​​and religions in the world. This diversity is a God-given destiny and should be accepted as a gift. In this context, religious moderation emerges as an approach that seems essential to preserving the gifts God has given us while promoting dialogue and cooperation between religious communities. This is the background for religious moderation seminar activities in Ladang Peris Village, Bajubang District, Batang Hari Regency. This activity was attended by 45 participants consisting of students, Village Officials, Ladang Peris Village Youth, Syara' Employees, and the General Public. The hope is to raise awareness about the importance of religious moderation and build cooperation and create a space for open and sustainable dialogue. The activity was held on Tuesday 14 January 2025 at the Ladang Peris Village Hall with the resource person, Head of Bajubang District KUA, Mr Arofah, S.H.I., M.H. The activity was carried out face to face with participants and resource persons who were in the same location, where the resource person provided material, then followed by a discussion and question and answer session. Overall, this activity provided a new and comprehensive view to all participants present at the Ladang Peris Village Hall regarding religious moderation.